Grammatical Error Analysis in Translating Conditional Sentences from Indonesia into English - Rika Yulia Siregar; Amelia Qolin Bulolo; Erikson Saragih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2022)
Conditional sentences is complex sentences (compound sentences) formed from a subordinate clause that starts with subordinate conjunction if it is in the conditional form (condition) and the main clause is the result. Studies on grammatical errors from student writing have been carried out by many previous researchers; however, research on conditional sentence translation errors is still very rarely conducted. This study aims to find out where students' mistakes in understanding the form of conditional sentence translation from Indonesian to English still often occur and to find the dominant type grammatical error. To achieve these objectives, this study used a qualitative descriptive research method with a research design. Data collection using text containing 30 sentence error types 1, 2, and 3 was conducted online through Google form of multiple-choice, short answers, and long answers. The subjects of this study were 20 7th semester students at the prima Indonesia university. The results found that final result of this study proved that the most common types of errors found in misformation were 241 or 32%, omission 228 or 30,2%, misordering 148 or 19,6%, and addition of 137 zor 18,1%. The results of the study concluded that the dominant errors found are misformation errors, which were the most frequent mistakes made by students. Recommended for students to study and improve their grammar and conditional sentences skills according to predetermined rules.